A clinically viable approach to restoring visual function using optogenetic gene therapy - Boyuan Yan; Suresh Viswanathan; Scott E. Brodie; Wen-Tao Deng; Kirsten E. Coleman; William W. Hauswirth; Sheila Nirenberg (Molecular Therapy: Methods & Clinical Development, 2023)
Optogenetic gene therapies offer a promising strategy for restoring vision to patients with retinal degenerative diseases, such as retinitis pigmentosa (RP). Several clinical trials have begun in this area using different vectors and optogenetic proteins (Clinical Identifiers: NCT02556736, NCT03326336, NCT04945772, and NCT04278131). Here we present preclinical efficacy and safety data for the NCT04278131 trial, which uses an AAV2 vector and Chronos as the optogenetic protein. Efficacy was assessed in mice in a dose-dependent manner using electroretinograms (ERGs). Safety was assessed in rats, nonhuman primates, and mice, using several tests, including immunohistochemical analyses and cell counts (rats), electroretinograms (nonhuman primates), and ocular toxicology assays (mice). The results showed that Chronos-expressing vectors were efficacious over a broad range of vector doses and stimulating light intensities, and were well tolerated: no test article-related findings were observed in the anatomical and electrophysiological assays performed.